Synthesizing method for co-production of acetamide and acetonitrile
The La-Zr/SiO2-γ-Al2O3 composite catalyst solves the problem of easy sintering of the catalyst at high temperature, and achieves efficient synthesis of acetamide and acetonitrile, prolongs the catalyst life, and significantly improves product conversion, selectivity and purity.
Patent Information
- Application Number
- CN202510286597.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-12
AI Technical Summary
The existing catalysts for synthesis of acetamide and acetonitrile are easily sintered at high temperatures, resulting in the problems of reduced activity and short life.
La-Zr/SiO2-γ-Al2O3 composite catalyst is used to fix La and Zr by monodispersing SiO2, and the La-Zr/SiO2 composite is connected to γ-Al2O3 using triethoxysilane to form spherical porous particles, reducing the agglomeration of precious metal particles and improving the stability and activity of the catalyst.
The life of the catalyst is extended, the conversion and selectivity of acetamide and acetonitrile are improved, and the purity of the product is significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of acetonitrile synthesis, and particularly relates to a synthesis method for the co-production of acetamide and acetonitrile. Background Art
[0002] Acetamide and acetonitrile, as key raw materials and solvents in the field of organic chemical industry, play an indispensable role in many downstream industries. They are important raw materials for the synthesis of various fine chemicals and polymer materials. In the pharmaceutical field, they are the key link in the synthesis of many drugs. At present, the acetic acid amination fixed bed synthesis process is generally used, with acetic acid and ammonia as raw materials, in the Al loaded with precious metals 2 O 3 Under the action of catalyst, acetamide and acetonitrile are synthesized by step-by-step dehydration. The chemical reactions involved in this method mainly include: CH 3 COOH+NH 3 →CH 3 CONH 2 +H 2 O、CH 3 COOH+NH 3 →CH 3 CN+2H 2 O、CH 3 CONH 2 →CH 3 CN+H 2 O, this method has a high conversion rate, few by-products, and high selectivity. Different products can be obtained by controlling the reaction temperature. However, the reaction requires a high temperature, and the catalyst has a short life at high temperatures and is easily deactivated.
[0003] Studies have shown that the melting point temperature (Tm) of precious metals commonly used as catalytic active components can reach above 1000°C. However, when the precious metal reaches 0.3Tm, the vibration of precious metal atoms on the interface intensifies and enhances the diffusion of precious metals. Precious metal atoms gradually migrate and aggregate to form larger particles, the dispersion decreases, and the specific surface area decreases, that is, the precious metal atoms sinter, which leads to a decrease in catalyst activity.
[0004] Patent CN117567320A discloses a method for preparing acetonitrile and co-producing acetamide by acetic acid ammoniation. The catalyst used in the patent is Co-Ni-Al 2 O 3 The metal in the catalyst can form a metal-carbon bond or a metal-nitrogen bond with the reaction substrate to stabilize the reaction intermediates, reduce the reaction activation energy, and promote the reaction. However, at high temperatures, the Co and Ni loaded on the surface of the catalyst will be sintered, reducing the contact area with the reactants, thereby reducing the catalyst activity or deactivating it. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for synthesizing acetamide and acetonitrile by co-production, so as to achieve the following invention objectives: to develop a composite γ-Al with high activity, high stability and long life. 2 O 3 Based acidic catalyst, it reduces the reaction temperature and promotes the synthesis of acetamide and acetonitrile.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for synthesizing acetamide and acetonitrile by co-production, comprising the following steps: (1) Mixing: After acetic acid and liquid ammonia are vaporized and preheated to 170-190°C, they are simultaneously introduced into a gas mixer and the outlet flow rate of the gas mixer is controlled at 0.29-0.31 m 3 / min, and then the mixed gas is introduced into a fixed bed reactor for reaction. The fixed bed reactor is filled with La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; (2) Production of acetamide: The reactor temperature is controlled at 210-230°C, the pressure is controlled at 0.58-0.62 MPa, the residence time of the mixed gas in the reactor is 25-35 seconds, and after the reaction is completed, it is passed into a distillation tower, and the pressure in the tower is controlled at 65-75 kPa, the tower top temperature is 75-85°C, the tower bottom temperature is 115-125°C, and the reflux ratio is 1.6-2.1. When the tower bottom liquid level remains unchanged, the tower bottom material is discharged, cooled and crystallized, and then dried at 35-45°C to constant weight to obtain acetamide; (3) Production of acetonitrile: The temperature of the reactor is controlled at 340-360°C, the pressure is controlled at 0.06-0.08 MPa, the residence time of the mixed gas in the reactor is 40-60 seconds, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled at 65-75 kPa, the top temperature is controlled at 75-85°C, the bottom temperature is controlled at 115-125°C, and the reflux ratio is controlled at 2-3. When the bottom liquid level remains unchanged, the top material is discharged and acetonitrile is obtained after cooling and dehydration; The mass ratio of acetic acid to ammonia in the mixed gas is 2.8-3.4:0.9-1.1; The La-Zr / SiO 2 -γ-Al 2 O 3 The preparation method of the composite catalyst comprises preparing a monodispersed SiO 2 , primary calcination, secondary calcination; The preparation of monodispersed SiO 2The method comprises the following steps: adding anhydrous ethanol and ammonia water to deionized water, stirring until the solution is clear and transparent, slowly dropping tetraethyl orthosilicate into the solution, reacting at a constant temperature of 28 to 32°C for 5.5 to 6.5 hours, and then centrifuging at a rate of 2500 to 3500 r / min for 4 to 6 minutes. After the lower precipitate is cleaned with deionized water and anhydrous ethanol, it is dried at 90 to 110°C for 15 to 25 minutes, and ground into a white powder with a particle size of 50 to 70 nm, i.e., monodispersed SiO 2 ; The mass ratio of anhydrous ethanol, ammonia water, deionized water and tetraethyl orthosilicate is 8-12:1.8-2.2:2.5-3.5:21-23; The mass fraction of ammonia in the ammonia water is 20 to 30%; The dropping time is 25 to 35 minutes.
[0007] The method of the primary calcination is to convert the monodispersed SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4 Add deionized water, then add glycine and polyethylene glycol acetone solution, after ultrasonic dispersion for 25 to 35 minutes, use ammonia water to adjust the pH value to 9 to 10, stir and react at 35 to 45°C for 2.4 to 2.6 hours, then centrifuge at 2500 to 3500 r / min for 4 to 6 minutes, wash the lower precipitate with deionized water, dry at 90 to 110°C for 15 to 25 minutes, transfer to 400 to 500°C for calcination for 3.5 to 4.5 hours, grind and crush into powder with a particle size of 70 to 90 nm, and obtain La-Zr / SiO 2 Complex; The monodisperse SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4 , the mass ratio of deionized water is 40-45:18-22:6-8:180-200; The monodisperse SiO 2 , the mass ratio of polyethylene glycol acetone solution to glycine is 20-22:4.5-5.5:2.9-3.1; The mass fraction of polyethylene glycol in the polyethylene glycol acetone solution is 0.4-0.6%; The stirring rate is 40-50 r / min.
[0008] The secondary calcination method is to 2 O3 , activated carbon, and then ground into powder with a particle size of 90 to 120 nm. 2 The composite was mixed evenly, and then triethoxysilane and deionized water were added, stirred and hydrolyzed for 25-35 minutes, dried at 45-55°C to constant weight, crushed and ground to form a powder of 0.8-1.2 μm to obtain an active matrix, and the active matrix was added to aluminum isopropoxide sol, ultrasonically dispersed for 25-35 minutes, and then dripped into an oil ammonia column drop by drop (controlling the dripping particle size to be 1.8-2.2 mm) to obtain a wet ball, dried until there was no moisture on the surface, dried at 100-120°C to constant weight, and heated to 550-650°C at a rate of 2-3°C / min, calcined at 550-650°C for 3.5-4.5 hours, and then cooled naturally to obtain spherical porous particles with a diameter of 1.8-2.2 mm, namely La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; The γ-Al 2 O 3 , activated carbon, La-Zr / SiO 2 The mass ratio of the composite, triethoxysilane and deionized water is 13-17: 1.3-1.5: 3.71-3.75: 2.2-2.6: 18-22; The mass ratio of the active matrix to the aluminum isopropoxide sol is 1.47-1.49: 26.45-26.49.
[0009] Compared with the prior art, the present invention has the following beneficial effects: Using monodispersed SiO 2 Adsorption of La(NO 3 ) 3 、Zr(NO 3 ) 4 Then, in an alkaline environment, La(NO 3 ) 3 、Zr(NO 3 ) 4 Precipitated on monodisperse SiO 2 Through calcination, La-Zr / SiO 2 The La-Zr / SiO 2 The complex is attached to γ-Al 2 O 3 Then, it was added into aluminum isopropoxide sol, and the wet ball was dried and calcined to obtain loaded La-Zr / SiO 2 γ-Al 2 O 3Spherical porous particles, namely La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst.
[0010] Monodisperse SiO 2 The pores of La and Zr can be well fixed, ensuring that the precious metal particles do not contact each other and reducing the agglomeration phenomenon at high temperatures. Triethoxysilane can fix La-Zr / SiO 2 The complex is fixed to γ-Al 2 O 3 Therefore, the catalyst has a long lifespan. When acetamide is continuously produced, the catalyst lifespan reaches 154 to 160 days, and when acetonitrile is continuously produced, the catalyst lifespan reaches 84 to 90 days. 2 The γ-Al2O3 has good dispersibility in aluminum isopropoxide sol. 2 O 3 La-Zr / SiO in spherical porous particles 2 The composite has good dispersion effect, and thus the catalyst activity is high. The conversion rate of acetamide reaches 99.51-99.64%, the selectivity reaches 91.89-92.11%, and the purity reaches 98.26-98.74%. The conversion rate of acetonitrile reaches 95.19-96.53%, the selectivity reaches 89.99-90.13%, and the purity reaches 99.83-99.91%. DETAILED DESCRIPTION
[0012] Example 1 A method for synthesizing acetamide and acetonitrile by co-production, comprising the following steps: (1) Mixing: After acetic acid and liquid ammonia are vaporized and preheated to 180°C, they are simultaneously introduced into a gas mixer and the outlet flow rate of the gas mixer is controlled at 0.3 m 3 / min, and then the mixed gas is introduced into a fixed bed reactor for reaction. The fixed bed reactor is filled with La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; (2) Production of acetamide: The temperature of the reactor is controlled at 220°C, the pressure is controlled at 0.6 MPa, the residence time of the mixed gas in the reactor is 30 s, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled to be 70 kPa, the top temperature is controlled to be 80°C, the bottom temperature is controlled to be 120°C, and the reflux ratio is controlled to be 1.8. When the bottom liquid level remains unchanged, the bottom material is discharged, cooled and crystallized, and then dried at 40°C to constant weight to obtain acetamide; (3) Production of acetonitrile: The temperature of the reactor is controlled at 350°C, the pressure is controlled at 0.07 MPa, the residence time of the mixed gas in the reactor is 50 s, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled to be 70 kPa, the top temperature is controlled to be 80°C, the bottom temperature is controlled to be 120°C, and the reflux ratio is controlled to be 2.5. When the bottom liquid level remains unchanged, the top material is discharged and acetonitrile is obtained after cooling and dehydration; The mass ratio of acetic acid to ammonia in the mixed gas is 3:1; The La-Zr / SiO 2 -γ-Al 2 O 3 The preparation method of the composite catalyst comprises preparing a monodispersed SiO 2 , primary calcination, secondary calcination; The preparation of monodispersed SiO 2 The method is as follows: anhydrous ethanol and ammonia water are added to deionized water, stirred until the solution is clear and transparent, and then tetraethyl orthosilicate is slowly added to the solution. After the addition is completed, the reaction is carried out at a constant temperature of 30°C for 6 hours, and then centrifuged at a rate of 3000r / min for 5 minutes. The lower precipitate is cleaned with deionized water and anhydrous ethanol, dried at 100°C for 20 minutes, and ground into a white powder with a particle size of 60nm, that is, monodispersed SiO 2 ; The mass ratio of anhydrous ethanol, ammonia water, deionized water and tetraethyl orthosilicate is 10:2:3:22; The mass fraction of ammonia in the ammonia water is 25%; The dropping time is 30 min.
[0013] The method of the primary calcination is to convert the monodispersed SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4 Add deionized water, then add glycine and polyethylene glycol acetone solution, after ultrasonic dispersion for 30 minutes, use ammonia water to adjust the pH value to 9.5, stir and react at 40°C for 2.5 hours, then centrifuge at 3000r / min for 5 minutes, wash the lower precipitate with deionized water, dry at 100°C for 20 minutes, transfer to 450°C for calcination for 4 hours, grind and crush into powder with a particle size of 80nm, and obtain La-Zr / SiO 2 Complex; The monodisperse SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4, the mass ratio of deionized water is 43:20:7:190; The monodisperse SiO 2 , the mass ratio of polyethylene glycol acetone solution and glycine is 21:5:3; The mass fraction of polyethylene glycol in the acetone solution of polyethylene glycol is 0.5%; The stirring rate is 45 r / min.
[0014] The secondary calcination method is to 2 O 3 , activated carbon, and then ground into powder with a particle size of 100 nm. 2 The composite was mixed evenly, and then triethoxysilane and deionized water were added, stirred and hydrolyzed for 30 minutes, dried at 50°C to constant weight, crushed and ground to form a 1 μm powder to obtain an active matrix, and the active matrix was added to aluminum isopropoxide sol, ultrasonically dispersed for 30 minutes, and then dripped into an oil ammonia column drop by drop (control the dripping particle size to be 2 mm) to obtain a wet ball, dried until there was no moisture on the surface, dried at 110°C to constant weight, and heated to 600°C at a rate of 2.5°C / min. After calcination at 600°C for 4 hours, the temperature was naturally lowered to obtain spherical porous particles with a diameter of 2 mm, namely La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; The γ-Al 2 O 3 , activated carbon, La-Zr / SiO 2 The mass ratio of the composite, triethoxysilane, and deionized water is 15:1.4:3.73:2.4:20; The mass ratio of the active matrix to the aluminum isopropoxide sol is 1.48:26.47.
[0015] Example 2 A method for synthesizing acetamide and acetonitrile by co-production, comprising the following steps: (1) Mixing: After acetic acid and liquid ammonia are vaporized and preheated to 170°C, they are simultaneously introduced into a gas mixer and the outlet flow rate of the gas mixer is controlled at 0.29 m 3 / min, and then the mixed gas is introduced into a fixed bed reactor for reaction. The fixed bed reactor is filled with La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; (2) Production of acetamide: The temperature of the reactor is controlled at 210°C, the pressure is controlled at 0.58 MPa, the residence time of the mixed gas in the reactor is 25 s, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled to be 65 kPa, the top temperature is controlled to be 75°C, the bottom temperature is controlled to be 115°C, and the reflux ratio is controlled to be 1.6. When the bottom liquid level remains unchanged, the bottom material is discharged, cooled and crystallized, and then dried at 35°C to constant weight to obtain acetamide; (3) Production of acetonitrile: The temperature of the reactor is controlled at 340°C, the pressure is controlled at 0.06 MPa, the residence time of the mixed gas in the reactor is 40 s, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled to be 65 kPa, the top temperature is controlled to be 75°C, the bottom temperature is controlled to be 115°C, and the reflux ratio is controlled to be 2. When the bottom liquid level remains unchanged, the top material is discharged and acetonitrile is obtained after cooling and dehydration; The mass ratio of acetic acid to ammonia in the mixed gas is 2.8:0.9; The La-Zr / SiO 2 -γ-Al 2 O 3 The preparation method of the composite catalyst comprises preparing a monodispersed SiO 2 , primary calcination, secondary calcination; The preparation of monodispersed SiO 2 The method is as follows: anhydrous ethanol and ammonia water are added to deionized water, stirred until the solution is clear and transparent, and then ethyl orthosilicate is slowly added to the solution. After the addition is completed, the reaction is carried out at a constant temperature of 28°C for 5.5 hours, and then centrifuged at a rate of 2500r / min for 4 minutes. The lower precipitate is cleaned with deionized water and anhydrous ethanol, dried at 90°C for 15 minutes, and ground into a white powder with a particle size of 50nm, that is, monodispersed SiO 2 ; The mass ratio of anhydrous ethanol, ammonia water, deionized water and tetraethyl orthosilicate is 10:2:3:21; The mass fraction of ammonia in the ammonia water is 20%; The dropping time is 25 min.
[0016] The method of the primary calcination is to convert the monodispersed SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4Add deionized water, then add glycine and polyethylene glycol acetone solution, after ultrasonic dispersion for 25 minutes, use ammonia water to adjust the pH value to 9, stir and react at 35°C for 2.4 hours, then centrifuge at 2500r / min for 4 minutes, wash the lower precipitate with deionized water, dry at 90°C for 15 minutes, transfer to 400°C for calcination for 3.5 hours, grind and crush into a powder with a particle size of 70nm to obtain La-Zr / SiO 2 Complex; The monodisperse SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4 , the mass ratio of deionized water is 40:18:6:180; The monodisperse SiO 2 , the mass ratio of polyethylene glycol acetone solution to glycine is 20:4.5:2.9; The mass fraction of polyethylene glycol in the acetone solution of polyethylene glycol is 0.4%; The stirring rate is 40 r / min.
[0017] The secondary calcination method is to 2 O 3 , activated carbon, and then ground into powder with a particle size of 90 nm. 2 The composite was mixed evenly, and then triethoxysilane and deionized water were added, stirred and hydrolyzed for 25 minutes, dried at 45°C to constant weight, crushed and ground to form a powder of 0.8 μm to obtain an active matrix, and the active matrix was added to aluminum isopropoxide sol, ultrasonically dispersed for 25 minutes, and then dripped into an oil ammonia column drop by drop (control the dripping particle size to be 1.8 mm) to obtain a wet ball, dried until there was no moisture on the surface, dried at 100°C to constant weight, and heated to 550°C at a rate of 2°C / min. After calcination at 550°C for 3.5 hours, the temperature was naturally lowered to obtain spherical porous particles with a diameter of 1.8 mm, namely La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; The γ-Al 2 O 3 , activated carbon, La-Zr / SiO 2 The mass ratio of the composite, triethoxysilane, and deionized water is 13:1.3:3.71:2.2:18; The mass ratio of the active matrix to the aluminum isopropoxide sol is 1.47:26.45.
[0018] Example 3 A method for synthesizing acetamide and acetonitrile by co-production, comprising the following steps: (1) Mixing: After acetic acid and liquid ammonia are vaporized and preheated to 190°C, they are simultaneously introduced into a gas mixer and the outlet flow rate of the gas mixer is controlled at 0.31 m 3 / min, and then the mixed gas is introduced into a fixed bed reactor for reaction. The fixed bed reactor is filled with La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; (2) Production of acetamide: The temperature of the reactor is controlled at 230°C, the pressure is controlled at 0.62MPa, the residence time of the mixed gas in the reactor is 35s, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled to be 75kPa, the top temperature is controlled to be 85°C, the bottom temperature is controlled to be 125°C, and the reflux ratio is controlled to be 2.1. When the bottom liquid level remains unchanged, the bottom material is discharged, cooled and crystallized, and then dried at 45°C to constant weight to obtain acetamide; (3) Production of acetonitrile: The temperature of the reactor is controlled at 360°C, the pressure is controlled at 0.08 MPa, the residence time of the mixed gas in the reactor is 60 s, and after the reaction is completed, it is passed into a distillation tower, the pressure in the tower is controlled to be 75 kPa, the top temperature is controlled to be 85°C, the bottom temperature is controlled to be 125°C, and the reflux ratio is controlled to be 3. When the bottom liquid level remains unchanged, the top material is discharged and acetonitrile is obtained after cooling and dehydration; The mass ratio of acetic acid to ammonia in the mixed gas is 3.4:1.1; The La-Zr / SiO 2 -γ-Al 2 O 3 The preparation method of the composite catalyst comprises preparing a monodispersed SiO 2 , primary calcination, secondary calcination; The preparation of monodispersed SiO 2 The method is as follows: anhydrous ethanol and ammonia water are added to deionized water, stirred until the solution is clear and transparent, and then ethyl orthosilicate is slowly added to the solution. After the addition is completed, the reaction is carried out at a constant temperature of 32°C for 6.5 hours, and then centrifuged at a rate of 3500r / min for 6 minutes. The lower precipitate is cleaned with deionized water and anhydrous ethanol, dried at 110°C for 25 minutes, and ground into a white powder with a particle size of 70nm, that is, monodispersed SiO 2 ; The mass ratio of anhydrous ethanol, ammonia water, deionized water and tetraethyl orthosilicate is 10:2:3:23; The mass fraction of ammonia in the ammonia water is 30%; The dropping time is 35 min.
[0019] The method of the primary calcination is to convert the monodispersed SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4 Add deionized water, then add glycine and polyethylene glycol acetone solution, after ultrasonic dispersion for 35 minutes, use ammonia water to adjust the pH value to 10, stir and react at 45 ° C for 2.6 hours, then centrifuge at 3500r / min for 6 minutes, wash the lower precipitate with deionized water, dry at 110 ° C for 25 minutes, transfer to 500 ° C for calcination for 4.5 hours, grind and crush into a powder with a particle size of 90nm to obtain La-Zr / SiO 2 Complex; The monodisperse SiO 2 、La(NO 3 ) 3 、Zr(NO 3 ) 4 , the mass ratio of deionized water is 45:22:8:200; The monodisperse SiO 2 , the mass ratio of polyethylene glycol acetone solution to glycine is 22:5.5:3.1; The mass fraction of polyethylene glycol in the acetone solution of polyethylene glycol is 0.6%; The stirring rate is 50 r / min.
[0020] The secondary calcination method is to 2 O 3 , activated carbon, and then ground into powder with a particle size of 120 nm. 2 The composite was mixed evenly, and then triethoxysilane and deionized water were added, stirred and hydrolyzed for 35 minutes, dried at 55°C to constant weight, crushed and ground to form a 1.2 μm powder to obtain an active matrix, and the active matrix was added to isopropanol aluminum sol, ultrasonically dispersed for 35 minutes, and then dripped into an oil ammonia column drop by drop (control the dripping particle size to be 2.2 mm) to obtain a wet ball, dried until there was no moisture on the surface, dried at 120°C to constant weight, and heated to 650°C at a rate of 3°C / min. After calcination at 650°C for 4.5 hours, the temperature was naturally cooled to obtain spherical porous particles with a diameter of 2.2 mm, namely La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst; The γ-Al 2 O 3 , activated carbon, La-Zr / SiO 2The mass ratio of the composite, triethoxysilane, and deionized water is 17:1.5:3.75:2.6:22; The mass ratio of the active matrix to the aluminum isopropoxide sol is 1.49:26.49.
[0021] Comparative Example 1 Based on Example 1, La-Zr / SiO 2 -γ-Al 2 O 3 In the preparation method of the composite catalyst, the preparation of monodispersed SiO 2 The first calcination is changed to La(NO 3 ) 3 、Zr(NO 3 ) 4 Add deionized water, then add glycine and polyethylene glycol acetone solution, after ultrasonic dispersion for 30 minutes, use ammonia water to adjust the pH value to 9.5, stir and react at 40°C for 2.5 hours, then centrifuge at 3000r / min for 5 minutes, wash the lower precipitate with deionized water, dry at 100°C for 20 minutes, transfer to 450°C for calcination for 4 hours, grind and crush into powder with a particle size of 80nm, and obtain La-Zr composite; in the secondary calcination step, La-Zr / SiO 2 The composite was changed to La-Zr composite.
[0022] Comparative Example 2 Based on Example 1, La-Zr / SiO 2 -γ-Al 2 O 3 In the preparation method of the composite catalyst, the addition of triethoxysilane and deionized water in the secondary calcination is omitted, and specifically, γ-Al 2 O 3 , activated carbon, and then ground into powder with a particle size of 100 nm. 2 The composite was mixed evenly, then added to aluminum isopropoxide sol, ultrasonically dispersed for 30 min, and then dripped into an oil-ammonia column drop by drop (control the dripping particle size to be 2 mm) to obtain a wet ball. After drying until there was no moisture on the surface, it was dried at 110 °C to constant weight, and then heated to 600 °C at a rate of 2.5 °C / min. After calcination at 600 °C for 4 h, the temperature was naturally cooled to obtain spherical porous particles with a diameter of 2 mm, namely La-Zr / SiO 2 -γ-Al 2 O 3 Composite catalyst.
[0023] Test Example 1 The conversion rate, selectivity and purity of acetamide and acetonitrile were calculated by the methods of Examples 1 to 3 and Comparative Examples 1 to 2, respectively. The calculation results are shown in Table 1.
[0024] Table 1
[0025] Test Example 2 The La-Zr / SiO prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were used respectively. 2 -γ-Al 2 O 3 The composite catalyst was used under the production conditions of Example 1 to continuously produce acetamide and acetonitrile, respectively, and the time required for the selectivity to be lower than 80% was recorded. The results are shown in Table 2.
[0026] Table 2
[0027] It can be seen from the above results that compared with Example 1, Comparative Example 1 does not use monodisperse SiO 2 Fixing La and Zr leads to agglomeration at high temperature, decreased catalyst activity, shortened life, and decreased product conversion, selectivity, and purity; Comparative Example 2: Triethoxysilane was not used to fix La-Zr / SiO 2 Composite with γ-Al 2 O 3 , La-Zr / SiO 2 With γ-Al 2 O 3 The combination is not strong, and the obtained catalyst undergoes La-Zr / SiO 2 Composite from La-Zr / SiO 2 The loss phenomenon will lead to a decrease in catalyst activity, shortened catalyst life, and decreased product conversion rate, selectivity, and purity.
Claims
1. A method for synthesizing acetamide and acetonitrile co-production, characterized in that: The synthesis method comprises mixing, preparing acetamide, and preparing acetonitrile; The mixing method is to vaporize acetic acid and liquid ammonia respectively and preheat them to 170-190°C, and then introduce them into a gas mixer at the same time, and control the outlet flow rate of the gas mixer to 0.29-0.31m 3 / min, and then the mixed gas is introduced into a fixed bed reactor filled with a La-Zr / SiO2-γ-Al2O3 composite catalyst; The preparation method of the La-Zr / SiO2-γ-Al2O3 composite catalyst comprises preparing monodispersed SiO2, calcining once, and calcining twice; The secondary calcination method comprises the following steps: grinding γ-Al2O3 and activated carbon to form a powder with a particle size of 90 to 120 nm, uniformly mixing the powder with a La-Zr / SiO2 complex, adding triethoxysilane and deionized water, stirring and hydrolyzing for 25 to 35 minutes, drying to constant weight, crushing and grinding to form a powder with a particle size of 0.8 to 1.2 μm, obtaining an active matrix, adding the active matrix to an isopropanol aluminum sol, ultrasonically dispersing the powder for 25 to 35 minutes, dripping the powder dropwise into an oil-ammonia column, controlling the dripping particle size to be 1.8 to 2.2 mm, obtaining a wet ball, drying the powder to constant weight, and calcining the powder to obtain spherical porous particles with a diameter of 1.8 to 2.2 mm, i.e., a La-Zr / SiO2-γ-Al2O3 composite catalyst.
2. A method for synthesizing acetamide and acetonitrile co-production according to claim 1, wherein the mass ratio of acetic acid to ammonia in the mixed gas is 2.8-3.4:0.9-1.1, the mass ratio of γ-Al2O3, activated carbon, La-Zr / SiO2 composite, triethoxysilane, and deionized water is 13-17:1.3-1.5:3.71-3.75:2.2-2.6:18-22, and the mass ratio of active matrix to aluminum isopropoxide sol is 1.47-1.49:26.45-26.
49.
3. A method for synthesizing acetamide and acetonitrile co-production according to claim 1, wherein the method for preparing acetamide is to control the reactor temperature at 210 to 230° C., the pressure at 0.58 to 0.62 MPa, the residence time of the mixed gas in the reactor at 25 to 35 s, and after the reaction is completed, the mixture is introduced into a distillation tower, the pressure in the tower is controlled to be 65 to 75 kPa, the tower top temperature is 75 to 85° C., the tower bottom temperature is 115 to 125° C., the reflux ratio is 1.6 to 2.1, and the tower bottom liquid level is unchanged, and the tower bottom material is output, and after cooling and crystallization, it is dried to constant weight at 35 to 45° C. to obtain acetamide.
4. A method for preparing acetonitrile by co-production of acetamide and acetonitrile according to claim 1, wherein the reactor temperature is controlled at 340 to 360° C., the pressure is controlled at 0.06 to 0.08 MPa, the residence time of the mixed gas in the reactor is 40 to 60 s, and after the reaction is completed, the mixed gas is introduced into a distillation tower, the pressure in the tower is controlled to be 65 to 75 kPa, the tower top temperature is 75 to 85° C., the tower bottom temperature is 115 to 125° C., the reflux ratio is 2 to 3, and after the tower bottom liquid level remains unchanged, the tower top material is output, and acetonitrile is obtained after cooling and dehydration.
5. According to the synthesis method of acetamide and acetonitrile co-production as described in claim 1, the method of the single calcination is to add monodisperse SiO2, La(NO3)3, and Zr(NO3)4 into deionized water, then add glycine and polyethylene glycol acetone solution, after ultrasonic dispersion, use ammonia water to adjust the pH value to 9-10, and stir the reaction at a constant temperature of 35-45°C for 2.4-2.6 h, then centrifuge, wash the lower precipitate, dry it, transfer it to 400-500°C for calcination for 3.5-4.5 h, grind it into powder with a particle size of 70-90 nm, and obtain La-Zr / SiO2 composite.
6. A method for synthesizing acetamide and acetonitrile co-production according to claim 5, wherein in the one-time calcination method, the mass ratio of monodisperse SiO2, La(NO3)3, Zr(NO3)4, and deionized water is 43:20:7:190, the mass ratio of monodisperse SiO2, acetone solution of polyethylene glycol, and glycine is 21:5:3, the mass fraction of polyethylene glycol in the acetone solution of polyethylene glycol is 0.5%, and the stirring rate is 45r / min.
7. The method for preparing monodisperse SiO2 by co-producing acetamide and acetonitrile according to claim 1, wherein anhydrous ethanol and aqueous ammonia are added to deionized water, stirred until the solution is clear and transparent, and then ethyl orthosilicate is slowly added dropwise to the solution. After the addition is complete, the reaction is carried out at a constant temperature of 28 to 32° C. for 5.5 to 6.5 hours, and then after centrifugation, the lower precipitate is cleaned, dried, and ground into a white powder with a particle size of 50 to 70 nm, i.e., monodisperse SiO2.
8. A method for synthesizing acetamide and acetonitrile co-production according to claim 7, wherein in the method for preparing monodisperse SiO2, the mass ratio of anhydrous ethanol, ammonia water and deionized water is 8-12:1.8-2.2:2.5-3.5, the mass fraction of ammonia in the ammonia water is 20-30%, and the dropping time is 25-35 min.
Citation Information
Patent Citations
One-step method for synthesizing nitrile by alcohol and / or aldehyde ammonification and dehydrogenation
CN101602691A
Preparation method of high-purity acetonitrile
CN117486756A
Method for preparing acetonitrile and co-producing acetamide by acetic acid ammoniation method
CN117567320A